Visual Preference of Infographics on Covid-19 - Romella M. Tuppal; Angelito E. Alvarado; Stephanie Shianne F. Acob; Althea L. Adriosula; Ivi Krizzle D. Agustin; Rowena Mae N. Agustin; Rioselle D. Alejandro (Humanistic Network for Science and Technology (HNST), 2021)
Visual communication has become a trend in health education during the COVID-19 pandemic specially the use of infographics. The purpose of this study is to determine the visual preference of the respondents on COVID-19 infographics with different language used among the residents of Ricarte Norte, Diffun, Quirino. Descriptive-correlational study was conducted among selected residents at Purok 4, Ricarte Norte, Diffun, Quirino through non-probability convenience sampling technique. Questionnaire consist of 2 parts. The first part focused on the profile of the respondents. On the other hand, the second part concentrated on the respondents’ perception regarding the visual preference of infographics on Covid-19 in terms of different designs and language used using the Likert scale. Data were gathered through face-to-face. The result revealed that the over-all visual preference of the respondents on COVID-19 infographics was “Fairly Preferred” but specifically, each group of the respondents exhibit unique and different visual preference on the COVID-19 infographics. The study revealed further that there was no significant difference as to the perception made by the respondents on their visual preference on the COVID-19 infographics and there exists a significant relationship between the assessed visual preference of the respondents on COVID-19 infographics with the used of the different language domain with their profile variables.Keywords: visual preference; infographics; covid-19